Eltrombopag for thrombocytopenia following allogeneic hematopoietic stem cell transplantation in children. Issue 5 (17th February 2020) - Masetti, Riccardo; Vendemini, Francesca; Quarello, Paola; Girardi, Katia; Prete, Arcangelo; Fagioli, Franca; Pession, Andrea; Locatelli, Franco
Abstract: Persistent thrombocytopenia is a common complication after allogeneic hematopoietic stem cell transplantation (HSCT). While the use of thrombopoietin receptor agonists was retrospectively investigated in adults, data in pediatric posttransplant thrombocytopenia are lacking. We evaluated the safety and efficacy of eltrombopag in nine children with platelet transfusion‐dependent persistent thrombocytopenia after HSCT. Eltrombopag was started at a median of 147 days after allo‐SCT and continued for a median period of 64 days, the starting dose being 50 mg per day. The therapy was well tolerated. After a median time of treatment of 36 days, eight patients (88%) reached sustained platelets count >50 000/μL.